Analisis CPU Threshold Storage Huawei Dorado V6000 pada Jaringan Storage Area Network dengan Metode Algoritma Decision Tree di PT. Berca Hardayaperkasa : - - Mohammad Rifqi Yasin; Fahlepi Roma Doni (Sci-tech Journal, 2024)
This aims to determine the CPU high or Controller Threshold on Huawei Doradoo V6000 Storage using the Decision Tree Algorithm Method, the process of data collection and research for this thesis was carried out in the period February to April 2024 with real data taken directly from Huawei Doradoo V6000 Storage, the method used in this research is the Decision Tree Algorithm, later it will facilitate decision making which aims to find out whether the CPU or Controller is experiencing Threshold or not the results of this study are expected to be an insight and one way or technique in knowing the CPU or Controller Threshold on Huawei Doradoo V6000 Storage. This research uses Quantitative Research which is a research that requires the use of many numbers in its research. The data used in this study is Primary Data, namely data sourced and obtained directly through the implementation of observations on the Huawei V6000 Storage Device. The basis for my consideration of taking this title is because the role of the CPU or Controller on Storage and Server is very important, the Controller on Storage and Server plays an important role in handling all types of computing tasks needed so that systems and applications can run properly. therefore this analysis is focused on how to analyze the High CPU on the Huawei V6000 Storage Device.